2023
DOI: 10.1007/s40519-023-01546-3
|View full text |Cite
|
Sign up to set email alerts
|

Early life influences on the development of food addiction in college attending young adults

Abstract: Purpose There is little investigation into the causes of food addiction. The aim of this study was to determine the impact of early life influences on the development of food addiction in college-attending young adults aged 18–29. Methods This study utilized a sequential explanatory mixed-methods research design. College-attending young adults were invited to complete an online survey measuring Adverse Childhood Experiences (ACEs), food addiction, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Feeding problems are common in childhood, a period considered critical for physical growth, neural development, and to shaping eating behaviors and habits that will continue into adulthood [ 1 3 ]. It is estimated that between 20% and 60% parents are concerned with their children’s feeding, having transient or persistent complaints that can compromise the family relationship [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feeding problems are common in childhood, a period considered critical for physical growth, neural development, and to shaping eating behaviors and habits that will continue into adulthood [ 1 3 ]. It is estimated that between 20% and 60% parents are concerned with their children’s feeding, having transient or persistent complaints that can compromise the family relationship [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, research has confirmed the following associations: (1) the link between parents using food to control the child's behavior (e.g., food pressuring or food rewarding) and more frequent binge-eating or dietary restraint [8], long-lasting food rejection [13], lower level of intuitive eating and higher level of disordered eating in adulthood [9]; (2) the association between parents applying restrictions or emotional regulation feeding and food preoccupation as well as emotional eating in adulthood [10,12]; (3) the link between positive and negative memories about family's food rules and dieting in adulthood [14]; and (4) the association between having regular family meals as a child and having regular family meals as an adult [15,23]. Moreover, the availability of unhealthy foods at home during childhood was associated with less healthful eating [24] and early life eating environments with the development of the food addiction [25] in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…candidates reported 2-3 times higher rates of childhood maltreatment and an increased risk for psychopathology independent of age, race, and sex 7 . Several explanations have been offered for this relationship including stressexacerbation, inflammation, even metabolic disturbances and altered eating patterns such as food addiction 8 .…”
mentioning
confidence: 99%